Productivity and profitability of pigeonpea (Cajanus cajan)-greengram (Vigna radiata) intercropping system under various moisture conservation practices in rainfed conditions - KAJE, V V; SHARMA, D K; MURALIKRISHNA, K S; BHATTACHARYYA, RANJAN (The Indian Journal of Agricultural Sciences, 2016)
Among cropping systems, 1:2 pigeonpea [Cajanus cajan(L) Millsp] greengram [Vigna radiata (L) Wilczek] intercropping had higher grain yields and economically feasible net returns. In case of moisture conservation practices, barley straw residue (mulch) @ 2.5 tonnes/ha had not only the better economic net returns, but also increased nutrient uptake due to incorporation of nutrients and sufficient moisture conservation in soils throughout cropping season. Although rainfall during the cropping season was sufficient and well distributed (hence moisture availability nearly same among all treatments except under dry spell), straw residue mulch had an advantage of addition of nutrients and organic fractions to the soil. Therefore, farmers can integrate 1:2 pigeonpea-greengram intercropping system without reducing spacing of the main crop and apply previous crop residues as mulch if possible. This not only conserves soil moisture during a dry spell period, but also enhances nutrients uptake under rainfed conditions.